PERANAN PENGGUNAAN MEDIA INTERNET CHATTING MIG 33 MENGGUNAKAN HANDPHONE PADA PERILAKU BERGAUL REMAJA - Meta Yuniar; Farida Nurfalah; Welly Wihayati (JURNAL SIGNAL, 2013)
The development of rapidly changing communications technology. With the development of communication technology audience communication patterns also changed significantly. Purpose of this research are: 1. To mengtahui how the communication process happens fellow chatters mig33 2. Fatherly mnegetahui how verbal and nonverbal language used by the chatter mig33 3. To find out how the behavior changes that occur within the chatter after using mig33 4. Fatherly figure out how to profit in mig33. In addition to a massive klahayak behavior, information technology is also changing the character and habits of the individual. One wrong in the present communication media is the internet. Technology of the Internet gave birth to so many social media. One is mig33 chat. Mig33 chat quite a role in the change of a person. It can be seen from mig33 world know personally before and after. In addition to having a negative impact, mig33 chat has a positive impact. Besides friendship, family ties, with mig33 chat is also a lot of business transactions that can be done